2008
DOI: 10.2214/ajr.07.3634
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Bone Complications After Radiation Therapy of Uterine Cervical Cancer: Evaluation with MRI

Abstract: Radiation-induced pelvic insufficiency fractures are a frequent complication of radiation therapy for uterine cervical cancer. Osteolysis and avascular necrosis of the femoral head were also diagnosed using MRI after radiation therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
126
5
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(140 citation statements)
references
References 35 publications
5
126
5
4
Order By: Relevance
“…A significant relationship was observed between treatment with radiotherapy and the occurrence of posttreatment fractures, which supports earlier studies demonstrating an increased risk of fracture in patients with NHL of bone, who were treated with radiation, particularly in high doses [33,46]. Other studies have also shown fractures to occur multiple years after radiation treatment and some investigators have suggested that fracture risk does not decrease over time [4,26,31,37]. Risk of fracture in our study did not appear to be related to the age or sex of the patient.…”
Section: Discussionsupporting
confidence: 82%
“…A significant relationship was observed between treatment with radiotherapy and the occurrence of posttreatment fractures, which supports earlier studies demonstrating an increased risk of fracture in patients with NHL of bone, who were treated with radiation, particularly in high doses [33,46]. Other studies have also shown fractures to occur multiple years after radiation treatment and some investigators have suggested that fracture risk does not decrease over time [4,26,31,37]. Risk of fracture in our study did not appear to be related to the age or sex of the patient.…”
Section: Discussionsupporting
confidence: 82%
“…7 The estimated incidence of pelvic insufficiency fracture (PIF) is between 10% and 29%. [8][9][10][11] Physicians must be aware of this complication that can impair the patient quality of life and must be distinguished from bone metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…The pelvic bones sustain radiation injury, varying in severity from radiation osteitis, stress fractures, and osteonecrosis to acute pathologic fractures in a dose dependent manner, with a threshold dose of approximately 3000 cGy [3,5,9,14]. Radiotherapy has also reportedly caused accelerated degenerative arthritis, leading to substantial pain and disability [7,19].…”
Section: Introductionmentioning
confidence: 99%